Teaching Speaking Model in Student Exchange MBKM Program in Indonesian Universities - Roni La'biran; Resnita Dewi (STAI Hubbulwathan Duri, 2023)
The goal of this research is to obtain a model in teaching speaking in Students Exchange MBKM program between PBSI Universitas Pancasakti Tegal and PBSI UKI Toraja. This research applies qualitative research. Sampling of data is students and lecturer PBSI from the University of Pancasakti Tegal, and Universitas Kristen Indonesia Toraja the research use total sampling. The instrument of this research used observation, interview, and questionnaire. In data analysis, researchers used qualitative methods. The results showed model of teaching speaking in students exchange MBKM program was Illustration, Interaction, Induction (III), Presentation, Practice, Production (PPP), and Mastery Learning. From the three models obtained based on field data, the model can be constructed into Contraction, Stimulation, Explanation, Demonstration, and Assessment.